Structural, metabolic and cognitive characteristics of cognitively unimpaired subjects with mismatching β‐amyloid biomarkers. (December 2021) - Salvadó, Gemma; Milà‐Alomà, Marta; Shekari, Mahnaz; Operto, Greg; Sánchez‐Benavides, Gonzalo; Cacciaglia, Raffaele; Falcon, Carles; Grau‐Rivera, Oriol; Arenaza‐Urquijo, Eider M.; Niñerola‐Baizán, Aida; Perissinotti, Andrés; Minguillón, Carolina; et al.
Abstract: Background: Several reports have described higher gray matter volumes and glucose consumption in cognitively unimpaired individuals with abnormal amyloid biomarkers, typically interpreted to be caused by inflammatory or compensatory mechanisms. In this study, we investigated structural and metabolic differences in cognitively unimpaired individuals with mismatching amyloid cerebrospinal fluid (CSF) and PET biomarkers (CSF+/PET‐), thought to be the earliest detectable Alzheimer's disease (AD) pathologic change. Additionally, we investigated whether inflammatory CSF biomarkers could explain such differences. Method: In 302 cognitively unimpaired participants of the ALFA study, we measured CSF Aβ42/40, phosphorylated tau (p‐tau), total tau (t‐tau), neurofilament light (NfL), neurogranin, sTREM2, YKL40, GFAP, IL6, S100b and α‐synuclein using the exploratory Roche NeuroToolKit assays, a panel of robust prototype immunoassays (Roche Diagnostics International Ltd). Participants also underwent T1 MRI, [ 18 F]flutemetamol amyloid PET, [ 18 F]FDG PET and cognitive assessment (PACC). Amyloid PET was quantified with a validated pipeline to render Centiloid (CL) values. Individuals were classified into three groups: CSF‐/PET‐, CSF+/PET‐ and CSF+/PET+ using previously determined thresholds for positivity (Aβ42/40<0.071 and CL>30). Between‐group differences in Gray Matter volume (GMv) and [ 18 F]FDG uptake were evaluated voxel‐wise with SPM12 (p<0.005, k>100) including age and sex as covariates. Additional models were implemented to measure possible mediation effects by inflammatory biomarkers (sTREM2, YKL40, GFAP, IL6, S100). Between‐group differences in cognition were also studied (p<0.05). Result: A total of 195 participants were CSF‐/PET‐, 82 were CSF+/PET‐ and 25 were CSF+/PET+ (Table 1). CSF+/PET‐ individuals displayed widespread higher GMv with respect to the reference CSF‐/PET‐ group as well as the CSF+/PET+ group (Fig. 1A). These differences were not mediated by inflammatory biomarkers. No significant between‐group differences were found in [ 18 F]FDG uptake. PACC values were significantly higher in CSF+/PET‐ than the other groups (Fig. 1B) Conclusion: In cognitively unimpaired individuals, increases in GMv and cognitive functioning were observed in participants ]with abnormal amyloid CSF but PET negative. These increases could not be explained by measured neuroinflammatory CSF biomarkers. Even at the earliest stages of the AD continuum, factors enhancing resistance to amyloid plaque deposition might have a beneficial impact on cognition and could be used to inform prevention strategies.